14. Penyutradaraan program documenter “membongkar layar tancap” Dengan gaya exspository - Rahmawati Perwita Sari (Saraswati)
Documentary art work entitles “Demolish Stuck Screen Movie” arranges stuck screen movie entertainment that represent watching movie entertainment at open place. This entertainment can emerge many social interactions for people who participate to enliven, so that the existence of this stuck screen movie bring positive effect for whole people. By defending its existence in modern era, the small of public areas and digital video disk and video compact disk plagiarism circulations that increasingly lead electronic industry make stuck screen movie entertainment beingignored. At the middle of entertainment attack, stuck screen movie starting to ignore, but stuck screen movie still become wanted entertainment and still become idol at capital side.This documentary work includes statement of journalist, show art observer, betawi artist and stuck screen movie entertainment businessman. In this art work creation, it applies three stages structure aimed to explain history of stuck screen movie till it does not success anymore and finally become nostalgia of film watching at open place. The using of expository style to make documentary program watcher easy to conclude message from all of demolish stuck screen movie story that aided by narration.This art work tries to give facts on problem that make stuck screen movie being aside. Modernism cannot be fought, but how we behave to keep surviving with all of ability and keeping innovation. Keyword: documentary, expository, stuck screen movie